The landscape of flipped classroom research: a bibliometrics analysis - Zhang, Fan; Wang, Hui; Zhang, Huachun; Sun, Qiuzi (Frontiers in Education, 2024)
The purpose of this study was to conduct a comprehensive review of existing research related to the flipped classroom and analyze it using bibliometrics.: The search strategy of Topic=("flipped classroom" or "invert classroom") was used to construct a representative dataset of flipped classrooms in the Web of Science Core Collection (Science Citation Index Expanded) database up to November 2022. Author and country collaboration networks, hotspot distribution clustering, and historical citation networks associated with flipped classrooms were visualized by VOSviewer (Version 1.6.18) and R-Studio (Version 1.4). Results: A total of 937 literature (868 articles and 69 reviews) were eventually included. The number of flipped classroom studies has increased dramatically since 2012. Europe, North America, China, and Australia have more research on flipped classrooms and have significant collaborations with other countries. Since flipped classrooms involve different subject areas and collaboration among authors is relatively fragmented. Numerous flipped classroom studies have been published in high-impact journals. The thematic trend suggests that the pros and cons of flipped classrooms and their application in medical education are possible research directions for some time to come.Although the flipped classroom has a relatively short history, it has received a lot of attention and is currently enjoying a high level of overall acceptance.The flipped classroom has been further practiced in medical education, and we look forward to seeing its application in more subject areas (e.g., linguistics, mathematics, and computer science.).